Soil Quality Improvement Using Compost and its Effects on Organic-Corn Production - . Riwandi; Merakati Handajaningsih; . Hasanudin; Ali Munawar (UNIVERSITY OF LAMPUNG, 2015)
Intensive agriculture has been well known to cause decline in soil organic matter and nutrient content of the soils. Therefore, efforts should be taken to avoid this from happening. Addition of organic fertilizers like compost has been increasingly become more important in Indonesian agriculture in the last couple of decades. The objectives of this study were to produce high quality compost using Indore method and to investigate its effects on organic-corn production. The study was conducted in the Integrated Agriculture Zone (IAZ), University of Bengkulu for two years (2012 and 2013). The study consisted of three steps: (i) soil fertility identification, (ii) compost production, and (iii) organic-corn field production. Soil fertility identification involved physical, chemical, biological analysis of soil samples collected from less fertile and moderately fertile soils. A randomized completely block design was employed in the field study which involved five rates of compost and two levels of soil fertility with three replications. In 2012, high quality compost was black, had pH 8, fine, odorless, and sufficiently high in NPK contents. Organic-corn yielded 2.94 and 5.69 Mg ha-1 of dried kernels on less fertile and moderately fertile soils, respectively at 20 Mg ha-1 compost. Similarly, in 2013 high quality compost was black, had pH 8, moderate, odorless, and high in NPK contents. The corn yields were 3.75 and 1.93 Mg ha-1 on less fertile and moderately fertile soils, respectively at 22.50 Mg ha-1 compost. [How to Cite: Riwandi, M Handajaningsih, Hasanudin, and A Munawar. 2015. Soil Quality Improvement Using Compost and its Effects on Organic-Corn Production. J Trop Soils 19: 11-19. Doi: 10.5400/jts.2015.20.1.11][Permalink/DOI: www.dx.doi.org/10.5400/jts.2015.20.1.11]